2023
DOI: 10.3390/toxics11040327
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exposure to Arsenic Affects Pupal Development and Neurological Functions in Drosophila melanogaster

Abstract: Millions of people in developing countries are affected by arsenic (As) toxicity and its prevalence. Arsenic’s detrimental effects on humans have been amplified by an unacceptable level of exposure to food and drinking water, the ongoing rise in industrial usage, and several other occupational conditions. Due to increased cellular absorption and the ability to cross the blood–brain barrier (BBB), inorganic arsenic (iAs) is extremely hazardous to living organisms in its trivalent form. Arsenic toxicity damages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Furthermore, it has been shown that As can cause toxicity in cells or tissues by increasing the generation of ROS and stimulating the damage of essential cellular biomolecules such as DNA, lipid, and proteins [ 40 , 41 ]. The toxic effects of acute arsenic treatment have also been described on the behaviour, cognition, and development of Drosophila melanogaster [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that As can cause toxicity in cells or tissues by increasing the generation of ROS and stimulating the damage of essential cellular biomolecules such as DNA, lipid, and proteins [ 40 , 41 ]. The toxic effects of acute arsenic treatment have also been described on the behaviour, cognition, and development of Drosophila melanogaster [ 42 ].…”
Section: Discussionmentioning
confidence: 99%